2013
DOI: 10.1017/s1368980013001870
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient intake and type 2 diabetes risk in middle-aged Australian women. Results from the Australian Longitudinal Study on Women's Health

Abstract: Objective: To investigate the association between macronutrient intake and type 2 diabetes risk in middle-aged Australian women. Design: A prospective cohort study, with 6 years (2002)(2003)(2004)(2005)(2006)(2007) of follow up. Dietary intake was assessed with a validated FFQ. Relative risks with 95 % confidence intervals were used to examine risk associations. Setting: Australian Longitudinal Study on Women's Health, Australia. Subjects: Australian women (n 8370) from the Australian Longitudinal Study on Wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…The positive associations of total and animal protein intakes with incident T2D in the MCCS were consistent with the results of some previous studies (5,6,9,32) but not of other studies (7,8,11). In the Dutch EPIC cohort of 38,094 participants with 918 new T2D cases (7), total and animal protein intakes were positively associated with incident T2D but not independent of BMI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The positive associations of total and animal protein intakes with incident T2D in the MCCS were consistent with the results of some previous studies (5,6,9,32) but not of other studies (7,8,11). In the Dutch EPIC cohort of 38,094 participants with 918 new T2D cases (7), total and animal protein intakes were positively associated with incident T2D but not independent of BMI.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, inconsistent findings regarding the association between protein intake and incident T2D have been reported in observational studies with long follow-up periods (5)(6)(7)(8)(9)(10). Some studies have revealed that higher total protein intake was associated with higher risk of incident T2D (5,6,9), whereas other studies observed no associations (7,8,11). Both the Health Professionals Follow-Up Study and EPIC (European Prospective Investigation into Cancer and Nutrition) study observed that animal protein intake was positively associated with diabetes, but no association was shown for plant protein (5,12).…”
Section: Introductionmentioning
confidence: 99%
“…Nine articles [17][18][19][20][21][22][23][24][25] were excluded from the systematic review because of overlapping populations. Out of these 22 articles, a total of 13 cohort studies [26][27][28][29][30][31][32][33][34][35][36][37][38] were appraised in the systematic review and metaanalysis. The 13 selected articles included in the systematic review were moderately heterogeneous in terms of population demographics, carbohydrate intake parameters, and the assessment of confounding factors.…”
Section: Search Resultsmentioning
confidence: 99%
“…The form of fat might also have affected the risk of diabetes. 35 Little is known about the consequences of lowcarbohydrate diets with respect to other chronic health problems, such as cancer, kidney disease, osteoporosis, and mental conditions. The biology that underlies the positive correlation between low-carbohydrate diets and all-cause death 8 has not yet been fully explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation